Perceptions of Exercise and Its Challenges in Patients With Nonalcoholic Fatty Liver Disease: A Survey‐Based Study. Issue 2 (26th October 2021) - Glass, Oliver; Liu, Daniel; Bechard, Elizabeth; Guy, Cynthia D.; Pendergast, Jane; Mae Diehl, Anna; Abdelmalek, Manal F.
Abstract : Exercise is a foundational treatment for nonalcoholic fatty liver disease (NAFLD); however, the majority of patients are unable to initiate and maintain effective exercise habits and remain at increased risk for progressive liver disease. Barriers and limitations to exercise in patients with NAFLD have not been fully identified. We performed a single survey of 94 patients with biopsy‐proven NAFLD to understand baseline physical activity and sedentary behavior, self‐perceived fitness, limitations to exercise, potential solutions to increase physical activity behavior, and perception of exercise as a foundational treatment for NAFLD. For exploratory analyses, we evaluated differences in responses to the survey by grouping severity of hepatic fibrosis as follows: nonalcoholic fatty liver (NAFL); early stage (nonalcoholic steatohepatitis [NASH] F0, NASH F1, NASH F2); and late stage (NASH F3, NASH F4). Zero weekly total physical activity was reported by 29% of patients with NAFLD. Late‐stage NASH had significantly lower vigorous ( P  = 0.024), walking ( P  = 0.029), total weekly activity ( P  = 0.043), and current fitness level ( P  = 0.022) compared to early stage NASH. Overall, 72% of patients with NAFLD reported limitations to exercise, with the greatest proportion citing lack of energy (62%), fatigue (61%), prior/current Injury (50%), and shortness of breath (49%). A preference for personal training to increase their physical activity was indicated by 66% of patients with NAFLD, and 63% preferred exercise over medication to treat NAFLD. Conclusion: The majority of patients with NAFLD have limitations to exercise but prefer exercise as a treatment option for NAFLD in the form of personal training. Patients with NAFLD may have unique physiologic limitations to exercise that worsen with fibrosis severity. Exercise interventions or services that are personalized and scalable may improve sustainability of exercise habits in the long term. Abstract : NAFLD patients have physiologic and behavioral limitations to physical activity and exercise that impact their ability to initiate and sustain exercise. These limitations may worsen with disease progression.